The significance of postbypass blood flow model in side to side bypass for moyamoya disease in predicting postoperative cerebral hyperperfusion syndrome - Wan, Guiping; Hu, Miao; Yu, Jin; Xin, Can; Tao, Tianshu; Quan, Wei; Chen, Jincao; Zhang, Jianjian (Frontiers in Neurology, 2024)
ObjectiveWe previously developed the use of side to side (s-s) bypass for the treatment of adult moyamoya disease (MMD) and discovered several kinds of distinct blood flow models intraoperatively, which we observed through indocyanine green-video angiography (ICG-VA). The purpose of this paper was to investigate the correlation between blood flow model (BFM) identified in s-s bypass and the incidence of postoperative cerebral hyperperfusion syndrome (CHS) among patients with MMD.MethodsWe analyzed 166 hemispheres from 153 patients diagnosed with MMD, including 118 hemispheres with s-s bypass and 48 with end to side (e-s) bypass. We categorized the enrolled patients into three pairs of comparison groups based on postoperative CHS (CHS or non-CHS) in s-s bypass, blood flow models (BFM I or BFM II) and surgical approach (s-s bypass or e-s bypass). Patients’ demographics and characteristics were compared between groups.ResultsAmong patients who developed CHS, the occurrence of BFM I was more frequent than that of BFM II (0.154 vs. 0.019, p = 0.029 < 0.05) and no significant differences were noted in the remaining data. In the group of blood flow models, the proportion of patients with a history of cerebral hemorrhage was higher in BFM II compared to BFM I (0.062 vs. 0.226, p = 0.009 < 0.05), and the incidence of severity of ischemia was found to be higher in BFM I than in BFM II (0.774 vs. 0.429, p = 0.011 < 0.05), while the postoperative modified Rankin Scale (mRS) score and the Matsushima grade displayed no obvious difference. In comparison with the occurrence of CHS in e-s bypass group (7/48, 0.146), s-s bypass group had no difference (11/118, 0.093; p = 0.323 > 0.05), BFM I group showed no discrepancy (10/65, 0.154, p = 0.906 > 0.05) while BFM II group was different (1/53, 0.019, p = 0.047 < 0.05).ConclusionThe proportion of postoperative CHS occurring in BFM II during s-s bypass was lower than that in e-s bypass and BFM I. The postbypass blood flow model in s-s bypass may serve as a novel predictor for postoperative CHS.